Systemic Immune Activation Leads to Neuroinflammation and Sickness Behavior in Mice. (10th July 2013) - Biesmans, Steven; Meert, Theo F.; Bouwknecht, Jan A.; Acton, Paul D.; Davoodi, Nima; De Haes, Patrick; Kuijlaars, Jacobine; Langlois, Xavier; Matthews, Liam J. R.; Ver Donck, Luc; Hellings, Niels; Nuydens, Rony
Abstract : Substantial evidence indicates an association between clinical depression and altered immune function. Systemic administration of bacterial lipopolysaccharide (LPS) is commonly used to study inflammation-associated behavioral changes in rodents. In these experiments, we tested the hypothesis that peripheral immune activation leads to neuroinflammation and depressive-like behavior in mice. We report that systemic administration of LPS induced astrocyte activation in transgenic GFAP-luc mice and increased immunoreactivity against the microglial marker ionized calcium-binding adapter molecule 1 in the dentate gyrus of wild-type mice. Furthermore, LPS treatment caused a strong but transient increase in cytokine levels in the serum and brain. In addition to studying LPS-induced neuroinflammation, we tested whether sickness could be separated from depressive-like behavior by evaluating LPS-treated mice in a panel of behavioral paradigms. Our behavioral data indicate that systemic LPS administration caused sickness and mild depressive-like behavior. However, due to the overlapping time course and mild effects on depression-related behavior per se, it was not possible to separate sickness from depressive-like behavior in the present rodent model.